90.6k views
2 votes
How would I simplify the rational expression x^2_2x-24÷ x^2+7x+12?

1 Answer

3 votes

we have the expression


(x^2-2x-24)/(x^2+7x+12)

step 1

Simplify the numerator


x^2-2x-24

Solve the quadratic equation, using the formula

a=1

b=-2

c=-24

substitute


x=\frac{-(-2)\pm\sqrt[]{(-2)^2-4(1)(-24)}}{2(1)}
\begin{gathered} x=\frac{2\pm\sqrt[]{100}}{2} \\ \\ x=(2\pm10)/(2) \end{gathered}

the values of x are

x=6 and x=-4

therefore


x^2-2x-24=(x+4)(x-6)

step 2

Simplify the denominator


x^2+7x+12

Solve the quadratic equation, using the formula

a=1

b=7

c=12

substitute


x=\frac{-7\pm\sqrt[]{7^2-4(1)(12)}}{2(1)}
x=(-7\pm1)/(2)

the values of x are

x=-3 and x=-4

therefore


x^2+7x+12=(x+3)(x+4)

step 3

substitute the given values in the original expression


((x+4)(x-6))/((x+3)(x+4))

simplify


(x-6)/(x+3)

User Jan Lehnardt
by
5.0k points